Liberty of conscience: in defense of America's tradition of religious equality - Nussbaum, Martha Craven (Basic Books, 2008)
A tradition under threat -- Living together : the roots of respect -- Proclaiming equality : religion in the new nation -- The struggle over accommodation -- Fearing strangers -- The establishment clause : school prayer, public displays -- Aid to sectarian schools : the search for fairness -- Contemporary controversies : the pledge, evolution, imagination, gay marriage, fear of Muslims -- Toward an "overlapping consensus"?